Aryl hydrocarbon receptor (Ahr)‐dependent Il‐22 expression by type 3 innate lymphoid cells control of acute joint inflammation. Issue 10 (18th March 2021) - Nehmar, Ramzi; Fauconnier, Louis; Alves‐Filho, Jose; Togbe, Dieudonnée; DeCauwer, Aurore; Bahram, Seiamak; Le Bert, Marc; Ryffel, Bernhard; Georgel, Philippe
Abstract: The aryl hydrocarbon receptor (AHR) controls several inflammatory and metabolic pathways involved in various diseases, including the development of arthritis. Here, we investigated the role of AHR activation in IL‐22‐dependent acute arthritis using the K/BxN serum transfer model. We observed an overall reduction of cytokine expression in Ahr ‐deficient mice, along with decreased signs of joint inflammation. Conversely, we report worsened arthritis symptoms in Il‐22 deficient mice. Pharmacological stimulation of AHR with the agonist VAG539, as well as injection of recombinant IL‐22, given prior arthritogenic triggering, attenuated inflammation and reduced joint destruction. The protective effect of VAG539 was abrogated in Il‐22 deficient mice. Finally, conditional Ahr depletion of Rorc ‐expressing cells was sufficient to attenuate arthritis, thereby uncovering a previously unsuspected role of AHR in type 3 innate lymphoid cells during acute arthritis.